Investigating the U.S. oil-macroeconomy nexus using rolling impulse responses - Marc Gronwald (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper is concerned with the apparent change in the U.S. oil price-macroeconomy relationship. It is investigated to what extent this change can be accounted for by the large oil price surges witnessed in the 1970s. The innovative approach of rolling impulse responses is applied and both the aggregate and the industry-level is considered. It is found that the first oil crisis has an persistent effect in the sense that this incident still dominates long-run results and superimposes both subsample and industry-specifics. The results, furthermore, suggest that the Great Moderation can essentially be explained by the non-occurrence of large oil shocks after the mid 1980s and that oil is less important for the economy than many researchers still believe.
Keywords: C32; C63; E32; 330; oil price; vector autoregressions; rolling impulse responses; Great Moderation; Mineralölpreisschock; Makroökonomischer Einfluss; Erdölpreis; Konjunktur; Konjunkturpolitik; USA